Impact of Mass Media on Cervical Cancer Screening and Awareness - Ayesha Shahid; Amna Javed; Amna Kazi; Faryal Irfan Abbasi; Muhammad Ikram; Rukiya Tariq (Achievements and Challenges of Medicine and Medical Science Vol. 10, 2025)
Background: Rising incidence of Cervical cancer besides being preventable and curable is quite an alarming situation. Lack of awareness in underdeveloped countries is one of the main reasons for its progress. This study aims to discover the role of mass media in cervical cancer and its screening awareness and what input we have given to its awareness. Materials and Methods: This is a Descriptive study conducted at the OPD of Gynecology and Obstetrics Department, Shaikh Zayed Hospital, Lahore, Pakistan from 1st August 2022 to 31st October 2022. Participants were selected via a convenient sampling technique. Data was analyzed through SPSS version 24. Results: Among all the respondents, 17% agreed that mass media has contributed to cervical cancer awareness while 83% were not familiar with the disease. Additionally, 93% and 7% of respondents had poor and good understanding, respectively. Moreover, 36% of respondents attained information from doctors/health care workers. Whereas, 68% and 32% of respondents had found mass media imperative and had not found significant in cervical cancer and its screening advocacy, respectively. Conclusion: The study revealed a poor understanding of cancer due to a lack of awareness but with the help of health care workers, and mass media, respondents’ knowledge of cervical cancer and its screening may be enhanced as well and awareness of their health spectrum may broaden. In Shaikh Zayed Hospital, cervical screening is up to the mark and every gynecological patient gets followed with cervical screening and managed accordingly. The institution raises awareness by counselling the patients regarding screening and getting their children vaccinated. It arranges seminars, class lectures, and OPD assignments to raise awareness.